Fatigue damage evolution in a particulate-reinforced metal matrix composite determined by acoustic emission and compliance method - Biermann, Horst; Vinogradov, Alexei; Hartmann, Oliver; Hartmann, Oliver (International Journal of Materials Research, 2021)
The damage evolution during fatigue of a particulate-reinforced metal matrix composite was investigated experimentally by two methods, i. e., by the measurement of the samples' stiffness values within individual stress - strain hysteresis loops and by the measurement and evaluation of the acoustic emission during cyclic deformation. Both methods indicate that the first damage occurs during the first loading cycle, in tension as well as in compression. After a short period of a high damage rate which is due to fracture of large particles, a longer range of a smaller damage rate follows, in which smaller particles break. Finally, both methods indicate the growth of the main (and final) fatigue crack.
CRIS-Team WoS Importer:2022-01-14